Basic density prediction of Eucalyptus sp. through the non-destructive ultrasound technique - Carvalho, Romário Alves (2023)
This work aimed to estimate the basic density of Eucalyptus sp. wood, using the non-destructive ultrasound technique. For this, 113 specimens with nominal dimensions of 2.5 x 2.5 x 57.5 cm (tangential x radial x longitudinal) were used, being in equilibrium humidity. To perform the density estimation, the three-dimensional model that governs the propagation of longitudinal waves in isotropic solids was used. The input variables of the model were determined, being the longitudinal modulus of elasticity by static bending, the Poisson's ratio by numerical methods and the propagation velocity of the ultrasound wave by a non-destructive ultrasound testing equipment. The basic density was also obtained by the hydrostatic balance method as a reference value. The actual average basic density was 595.40 kg.m-3 and the estimated one was 591.21 kg.m-3. The estimated value had a strong correlation with the observed value with r =0.89. The estimation by the three-dimensional model showed a low error with an RMSE of 6.50% and a bias of 0.59%. The estimation of the basic density using this method obtained good precision, being similar to the resistography technique.